Pengaruh Gaya Kepemimpinan Transformasional Dan Lingkungan Kerja Fisik Terhadap Produktivitas Kerja Karyawan Pada Lawless Burgerbar Cabang Kemang Jakarta Selatan - Reza Anandria; Henni Marlinah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to examine the influence of Transformational Leadership Style and Physical Work Environment on Employee Work Productivity at Lawless Burgerbar Cabang Kemang Jakarta Selatan, both separately and simultaneously. The method used was a Saturated Sample with a population of 36, where all members of the population were made respondents. Data were collected through observation and questionnaires, and analyzed using validity, reliability, classical assumptions, regression, correlation coefficients, determination coefficients, and hypothesis tests. The results showed that the Transformational Leadership Style had a significant influence on Employee Work Productivity (tcal > table) with a regression equation of Y = 7.456 + 0.502X1, as well as a correlation value of 0.446 indicating a moderate relationship. The Physical Work Environment also has a significant effect on Employee Work Productivity (tcal > table) with a regression equation Y = 7.456 + 0.474X2 and a correlation of 0.461 which indicates a moderate relationship. Simultaneously, these two variables affected Employee Work Productivity (F to calculate > Ftable) with a regression equation Y = 7.456 + 0.502X1 + 0.474X2 and a correlation value of 0.461, indicating a moderate relationship, while a determination coefficient of 54.9% indicated that 45.1% was influenced by other factors. This means that if there is an increase in the variables of transformational leadership style and physical work environment, employee work productivity will also increase. The variable that has the most dominant influence on employee work productivity is the physical work environment variable of 46.1%.